2009
DOI: 10.1002/ibd.20940
|View full text |Cite
|
Sign up to set email alerts
|

Obestatin/ghrelin ratio: A new activity index in inflammatory bowel diseases

Abstract: Ghrelin and obestatin seem to play a significant role in IBD pathogenesis. Further studies are needed to elucidate the role of these hormones as new biological markers of activity of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
2
23
1
3
Order By: Relevance
“…Plasma obestatin levels were high in anorexia nervosa and epileptic patients compared to normal subjects [19,21,22,[53][54][55][56][57][58][59][60]. Obestatin seem to play a significant role in the pathophysiology of these diseases.…”
Section: Biological Activitiesmentioning
confidence: 82%
“…Plasma obestatin levels were high in anorexia nervosa and epileptic patients compared to normal subjects [19,21,22,[53][54][55][56][57][58][59][60]. Obestatin seem to play a significant role in the pathophysiology of these diseases.…”
Section: Biological Activitiesmentioning
confidence: 82%
“…It is known that the chronic inflammation present in uremic patients undergoing HD plays a key role, since it is a relevant factor for cardiovascular risk, and is correlated with obesity. It has been shown in various studies that obestatin plays a role in pathologic processes, without altering, at least initially, renal function in which the inflammation plays a key role from a physiopathological viewpoint, as in rheumatoid arthritis and in chronic inflammatory intestinal disease [18,19] . Our findings confirm this correlation, evidencing a strong and independent correlation between PCR and obestatin, thus indicating that this hormone may play a physiopathological role in the complex process of inflammation characterizing the uremic patient.…”
Section: Discussionmentioning
confidence: 99%
“…pylori infection [10]. Other reports showed that plasma G/O ratio is related to inflammatory bowel diseases and obesity [12, 18, 19]. …”
Section: Introductionmentioning
confidence: 99%